Linear IgA Dermatosis in a Child: Clinical Case - Nikolay N. Murashkin; Alexander I. Materikin; Roman V. Epishev; Maria A. Leonova; Leonid A. Opryatin; Roman A. Ivanov; Alena A. Savelova; Oksana R. Katunina; Kirill A. Kulikov; Daniel R. Danielyan (Вопросы современной педиатрии, 2023)
Background. Linear IgA dermatosis is a rare autoimmune bullous disease characterized by vesiculo-bullous subepidermal lesions (affecting the skin and mucous membranes) and by linear homogeneous IgA deposition in the epidermis basal membrane.Clinical case description. Clinical case of linear IgA dermatosis in children is presented. Clinical data assessment, histological examination of the skin biopsy (to determine the depth of bullous), immunofluorescent examination (to reveal IgA deposition in the epidermis basal membrane) are crucial for reliable disease diagnosis according to the studies. Altogether it helps to establish the final diagnosis and determine the patient's management. Dapsone is the first-line treatment for this disease, it has proven to be an effective and safe medication.Conclusion. This case of linear IgA dermatosis is of concern due to disease severity and its rarity in clinical practice. Differential diagnosis is rather complicated and clinically requires high-tech research methods. Only immunofluorescent examination allows to diagnose linear IgA dermatosis accurately. Lesions' regression was achieved due to systemic therapy with dapsone (1.8 mg/kg/day).